Analisis Yuridis terhadap Peran TNI AL dalam Kerjasama Regional Terkait Pemberantasan Perompakan Bersenjata di Selat Malaka - Ahmad Suberlian N; Alfredo Panataran Purba; Edvien Adi Putra (Lembaga Kajian Pertahanan Strategis, 2024)
The Strait of Malacca is one of the busiest shipping lanes in the world connecting the Indian Ocean with the South China Sea, but is also vulnerable to armed piracy activities that threaten regional and global security. This threat requires a collective response and effective coordination from the countries involved. This research aims to evaluate the role of the Indonesian Navy (TNI AL) in regional cooperation to eradicate piracy in the Malacca Strait, as well as to analyze the effectiveness of this cooperation in reducing piracy incidents. The research method used is a literature study which involves analysis of legal documents, books, journal articles and information from official websites. Primary data was obtained from Law Number 34 of 2004 concerning the TNI and international regulations such as UNCLOS 1982, while secondary data came from literature on maritime law and regional security. The Indonesian Navy has played an active role in regional cooperation through initiatives such as the Malacca Strait Patrols (MSP) and the Regional Cooperation Agreement on Combating Piracy and Armed Robbery against Ships in Asia (ReCAAP). Joint patrols and information exchange through the ReCAAP Information Sharing Center (ISC) have succeeded in reducing piracy incidents in the Malacca Strait. However, there are still challenges such as differences in naval capacity and coordination obstacles between countries that affect the effectiveness of this cooperation.